Interaction of Zap70 and CXCR4 receptor at lamellipodia that determines the directionality during Jurkat T cells chemotaxis. (October 2017) - Wu, Chia-Yun; Tsai, Yi-Ying; Chen, Sheng-Yi; Lin, Yu-Ping; Shin, Jyh-Wei; Wu, Chia-Ching; Yang, Bei-Chang
Highlights: Zap-70 controls the direction of lamellipodia formation. Zap-70 modulates the cell adhesion capability. Zap-70/CXCR4 complex located at cell membrane modulates directional migration of T cells. Abstract: Directional migration of T-lymphocytes is a key process during immune activation and is tightly regulated both temporally and spatially. The initial cell membrane protrusion at a particular site is critical for determining the direction of cell migration. In this study, we found that ZAP-70 protein appeared not only at the margin of the spreading areas of polarized Jurkat T cells but also formed clusters near the center of the cell body on a fibronectin plate. Specifically, some pZAP-70 was located at the lamellipodia/filopodia and was closely associated with the most extended membrane contact. To visualize the dynamic distribution of ZAP-70 on migrating Jurkat T cells, we generated a fluorescent ZAP-70-EGFP fusion protein (hZAP70G). Expression of the hZAP70G in P116 cells, a ZAP-70 defective Jurkat derivative, restored its chemotactic migration toward SDF-1, adhesion to fibronectin matrix, and integrin activation. In addition, the distribution of hZAP70G protein is associated with changes in cell shape, specifically the membrane protrusion step, forming filopodia/lamellipodia and a retracting uropod. Furthermore, SDF-1 stimulated the formation of ZAP-70 and CXCR4 complex. CXCR4 was observed mainly at the leading edge of migrating cell. The localization of ZAP-70 at the very front edge of protruding lamellipodia was close to CXCR4 and a part of them were overlapped. Collectively, our data describe the critical early step of directional cell movement toward SDF-1 that ZAP-70 is recruited to the CXCR4 at the leading edge of membrane and consequently modulates lamellipodia/filopodia formation and integrin activation.